2019
DOI: 10.3390/ijerph16234798
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Agriculture Workers to Pesticides: The Effect of Heat on Protective Glove Performance and Skin Exposure to Dichlorvos

Abstract: Dichlorvos is a toxic organophosphate insecticide that is used in agriculture and other insecticide applications. Dermal uptake is a known exposure route for dichlorvos and chemical protective gloves are commonly utilized. Chemical handling and application may occur in a variety of thermal environments, and the rates of both chemical permeation through gloves and transdermal penetration may vary significantly with temperature. There has been no published research on the temperature-dependent kinetics of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Consequently, various classes of pesticides targeting specific pests are being produced to promote increased and quality crop yields. Dichlorvos (2,2-dichlorovinyl dimethyl phosphate) is one of the most commonly used organophosphate pesticide with insecticidal properties and often applied on crops, stored products and in treatment of animals [ 2 , 3 ]. It has been used to eliminate crustacean ectoparasites in fish farming [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, various classes of pesticides targeting specific pests are being produced to promote increased and quality crop yields. Dichlorvos (2,2-dichlorovinyl dimethyl phosphate) is one of the most commonly used organophosphate pesticide with insecticidal properties and often applied on crops, stored products and in treatment of animals [ 2 , 3 ]. It has been used to eliminate crustacean ectoparasites in fish farming [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also noticeable is the fact that the reported kP values show an inverse correlation with the logKo/w of the tested substances (Figure 2), and are in poor accordance with results from other experimental works (Peckham et al, 2017;Thredgold et al, 2019). For an additional example, the top kP value obtained by Sartorelli et al (1998) for dimethoate (Table I) contrasts with the results by Nielsen et al (2004) which observed no permeation of this pesticide through human skin during 48-hour assays.…”
Section: Sartorellimentioning
confidence: 51%
“…Dermal exposure to polycyclic aromatic hydrocarbons (PAHs) and organophosphorus pesticides (OPPs) is an important concern (Beitel et al, 2020;Fent et al, 2020;Peckham et al, 2017;Thredgold et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the respondents knew of oral route of exposure and a considerable majority was unaware of other routes of exposure such as skin and respiratory tract. Thredgold et al (2019) re-emphasized the important role of dermal exposure in pesticide-induced toxicity in farm workers with almost 500-fold increased cumulative permeability of DDVP under elevated farm environmental temperature. Exposure to sunlight induces photodegradation of organophosphates including DDVP which generates reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Despite personal experiences of poisoning, most of them did not use personal protective equipment or believe failure to wear protective clothes/equipment was hazardous to health. The role of personal protective equipment has been emphasized and proven by previous researchers as a means of preventing occupational exposure to pesticides (MacFarlane et al, 2013;Thredgold et al, 2019). Also, a vast majority was unaware of withdrawal periods and as such was not observing them.…”
Section: Discussionmentioning
confidence: 99%